2011
DOI: 10.1017/s0007485311000411
|View full text |Cite
|
Sign up to set email alerts
|

Lower temperature thresholds for oviposition and egg hatching of the Red Palm Weevil, Rhynchophorus ferrugineus (Coleoptera: Curculionidae), in a Mediterranean climate

Abstract: The red palm weevil, Rhynchophorus ferrugineus Olivier (Coleoptera: Curculionidae), is an economically important pest of palms worldwide. To better understand the phenology of R. ferrugineus populations in the Mediterranean basin, the objective of the present work has been to estimate the effect of temperatures within the range 10-25°C on the reproductive parameters of R. ferrugineus and to determine its lower temperature thresholds for oviposition and egg hatching. Our results confirm that oviposition in R. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 8 publications
3
16
1
Order By: Relevance
“…Recommendations on the number of applications and doses should probably take into account the size of the palms as well as the bioecology of this pest. In the Northern Mediterranean Basin, oviposition and egg hatching periods extend from early April to mid‐October/early November and from mid‐March to mid/late October respectively . Therefore, palms should be protected for about 7 months per season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations on the number of applications and doses should probably take into account the size of the palms as well as the bioecology of this pest. In the Northern Mediterranean Basin, oviposition and egg hatching periods extend from early April to mid‐October/early November and from mid‐March to mid/late October respectively . Therefore, palms should be protected for about 7 months per season.…”
Section: Discussionmentioning
confidence: 99%
“…In the Northern Mediterranean Basin, oviposition and egg hatching periods extend from early April to mid-October/early November and from mid-March to mid/late October respectively. 42 Therefore, palms should be protected for about 7 months per season. As the effect of winter temperatures on the population dynamics of R. ferrugineus could be a synchronisation of the whole population, 41,48 a spray treatment targeting newly emerged adults in late March/early April could be followed by a stipe injection in mid/late April.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zhao and Ju29 reported a survival rate for the generation of R. ferrugineus of only 10.0% at 19 °C. However, there are some contradictory data from other studies: Dembilio & Jacas5 and Dembilio et al 12 found that the threshold temperature for egg hatching was less than 14 °C on apple slices. These apparently contradictory differences may be attributable to geographical conditions, host plants, or other factors2630.…”
Section: Discussionmentioning
confidence: 89%
“…To date, the thermal requirements and the lower temperature thresholds for development, oviposition, and egg hatching in R. ferrugineus have been described512 along with effects on emergence13 and population growth14. However, there is limited information on how temperature affects population demographics and age- and stage-specific traits, which are important for metamorphic insects15.…”
mentioning
confidence: 99%
“…Golden Delicious, 1.00 ± 0.10 cm thick, surface 14.15 ± 1.00 cm 2 ) were placed as substrate for female feeding and oviposition. Apples were chosen as the substrate because accurate detection of feeding holes or eggs in natural substrate (palm tissue) is not possible, and weevils readily feed and oviposit on apples . One of the apple slice substrates was treated by applying the test chemical at the centre of the substrate using a glass syringe for gas chromatography (Hamilton®), while the other substrate was left untreated.…”
Section: Methodsmentioning
confidence: 99%